Comparison of splinting, splinting plus local steroid injection and open carpal tunnel release outcomes in idiopathic carpal tunnel syndrome - YAĞCI, İLKER (SPRINGER, 2006)
The objective of this study was to compare the short- and long-term efficacies of splinting (S), splinting plus local steroid injection (SLSI), and open carpal tunnel release (OCTR) in mild or moderate idiopathic carpal tunnel syndrome (CTS). Patients with mild or moderate idiopathic CTS who experienced symptoms for over 6 months were included in the study. The patients were evaluated for the baseline and the third and sixth month scores after treatment. Follow-up criteria were ENMG parameters, Boston Questionnaire, and patient satisfaction. Fifty-seven hands completed the study. Twenty-three hands had been splinted for 3 months. Twenty-three hands were given a single steroid injection and splinted for 3 months, and 11 hands were operated. In the first 3 months, all treatment methods provided significant improvements in both clinical and EMG parameters in which OCTR had better outcomes on median sensorial nerve velocity at palm wrist segment. In the second 3 months, while the clinical and EMG parameters began to deteriorate in S and SLSI group, OCTR group continued to improve, and BQ functional capacity score of OCTR group was statistically better than that in conservative methods (P = 0.03). S and SLSI treatments improved clinical and EMG parameters comparable to OCTR in short term. However, these beneficial effects were transient in the sixth month follow-up and OCTR was superior to conservative treatments.
Keywords: idiopathic carpal tunnel syndrome; splinting; corticosteroid injection; surgery; ADMINISTERED BOSTON QUESTIONNAIRE; RANDOMIZED CONTROLLED TRIAL; ELECTROPHYSIOLOGICAL FINDINGS; EFFICACY; TERM